Urological Complications in Patients Undergoing Hemodialysis and Peritoneal Dialysis: Urological Complications in Hemodialysis and Peritoneal Dialysis - Kundi, Rizwan; Khan, Zafar Ahmad (Pakistan Journal of Health Sciences, 2025)
Urological complications (UCs) remain a significant concern following kidney transplantation (KT), contributing to both morbidity and mortality. Objectives: To determine the prevalence of urological complications and associated factors in patients receiving hemodialysis (HD) and peritoneal dialysis (PD). Methods: A comparative cross-sectional study was conducted in the Department of Urology at Bacha Khan Medical College and Mardan Medical Complex, Mardan. A tertiary hospital, involving 310 dialysis patients. Data on demographics, comorbidities, and urological complications were collected. Urological complications assessed included urinary tract infections (UTI), bladder dysfunction, nephrolithiasis, hematuria, and urethral stricture. Laboratory tests were used to evaluate renal function parameters. T-tests discover differences between groups, and chi-squares are used for identifying differences in categorical data. If the p-value was less than 0.05, the result regarded as statistically significant. Results: The mean age of participants was 58.7 ± 12.3 years, and the majority were male (58.1%). Diabetes and hypertension were prevalent in 45.8% and 71.0% of patients, respectively. The prevalence of urological complications included UTIs (27.4%), bladder dysfunction (19.4%), LUTS (29.7%), hematuria (15.5%), and nephrolithiasis (11.3%). HD patients had a significantly lower residual urine output compared to PD patients (80 mL/day vs. 200 mL/day, p<0.001). UTI and bladder dysfunction were significantly more common in diabetic patients (p=0.03 and p=0.02, respectively). Patients who received dialysis for longer duration had more LUTS (p=0.03). There was a significant difference in albumin levels between HD patients and PD patients (p=0.04). Conclusions: Urological complications are common in dialysis patients, with significant associations observed with dialysis modality, diabetes, and residual urine output.